2011
DOI: 10.4141/cjss10067
|View full text |Cite
|
Sign up to set email alerts
|

Clay mineralogy and chemical properties of argillic horizons in central Yukon paleosols

Abstract: Daviel, E., Sanborn, P., Tarnocai, C. and Smith, C. A. S. 2011. Clay mineralogy and chemical properties of argillic horizons in central Yukon paleosols. Can. J. Soil Sci. 91: 83–93. Wounded Moose paleosols occur on Middle Pleistocene and older glacial deposits in central Yukon, and exhibit thick sola with distinctive reddish brown argillic (Bt) horizons. Extensive field investigations in the mid-1980s documented the distribution, morphology, and standard physical and chemical properties of these paleosols, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The BC and C horizons of penultimate till also have chlorite, chlorite intergrades, and vermiculite with only a small amount of smectite. (Bond and Sanborn 2006) and from Bt horizons in pre-Reid age soils in the central Yukon (Daviel et al 2011); values are similar to those obtained at weathered bedrock sites adjacent to our sampling locations (Dampier et al 2011).…”
Section: Clay Mineralogysupporting
confidence: 88%
“…The BC and C horizons of penultimate till also have chlorite, chlorite intergrades, and vermiculite with only a small amount of smectite. (Bond and Sanborn 2006) and from Bt horizons in pre-Reid age soils in the central Yukon (Daviel et al 2011); values are similar to those obtained at weathered bedrock sites adjacent to our sampling locations (Dampier et al 2011).…”
Section: Clay Mineralogysupporting
confidence: 88%
“…The authors concluded that these deposits had a similar alteration history and were subjected to moderate weathering. For cold-climate regions, Daviel et al (2011) inferred an average value of 74.4 in a paleosol located in central Yukon; these authors propose that values near 75 show a considerable proportion of primary minerals converted into clay minerals. In Siberia, Zech et al (2008) identified values of CIA > 63 that they interpreted as being related to intense weathering processes.…”
Section: Geochemical Properties Of the Sedimentsmentioning
confidence: 99%
“…Chemical weathering in periglacial areas is also an important mechanism in terms of geomorphic work (Allen et al, 2001;Thorn et al, 2001), being controlled by the type of lithology, biological activity, organic matter, topography, aspect, water availability, the structure of the hydrologic system and the age of exposure/deglaciation (Egli et al, 2014). Previous work developed indexes, such as the chemical index of alteration (CIA) (Daviel et al, 2011), to assess soil weathering based on geochemical properties, .…”
Section: Introductionmentioning
confidence: 99%
“…Chemical weathering in periglacial areas is also an important mechanism in terms of geomorphic work (Allen et al, 2001;Thorn et al, 2001), being controlled by the type of lithology, biological activity, organic matter, topography, aspect, water availability, the structure of the hydrologic system and the age of exposure/deglaciation (Egli et al, 2014). Previous work developed indexes, such as the chemical index of alteration (CIA) (Daviel et al, 2011), to assess soil weathering based on geochemical properties, .…”
Section: Introductionmentioning
confidence: 99%